Prevalence of HPV16 IgG Antibody and Rt-Pcr DNAdetection in Patients with Laryngeal Carcinoma and Cervical Dysplasia - Georgi Nikolov; Milena Karcheva; Chavdar Tsvetkov; Alexandar Valkov; Rashev R.; Alexandar Blazhev (Journal of Biomedical & Clinical Research)
Human papillomaviruses (HPVs) are associated with the most common sexually transmitted infections. It is well documented that high-risk (HR)-HPVtypes are etiologically associated with some cancers. The aim of the study was to investigate HPV16-DNApositivity and prevalence of Ig Gantibody against HPV16 in patients with laryngeal carcinoma and precancerous lesions of cervix uteri in Pleven region, Bulgaria. Material/Methods: We performedacross-sectional study and investigated clinical materials. Attached is real-time PCR-analysis for detection of HPV16-DNA. HPVspecific antibody response by enzyme-linked immunosorbent assay (ELISA) test for detection and quantification of specific Ig Gantibodies in serum were used. Results: For the six-month period, 30 samples were collected and tested. Fourteen of them were found in patients with carcinoma of the larynx and sixteen - in patients with various lesions of cervix uteri.We found that six patients (42.8%) in the first group and eight patients (50%) in the second group were HPV16-DNA-positive. Different age groups were affected. The sera analyzed in this study showed that seven patients (50%) with carcinoma of the larynx were seropositive of whom four (57%) were males. Fourteen of the females with dysplasia (88%) were seropositive. Matching DNApositivity and antibody response were found in 29%of the patients with laryngeal cancer. The match was found in 50%of the females with cervical dysplasia. Conclusions: Real-time PCRisarapid, cost-effective method for detection of HPVs.Ahigh level of seropositivity was found in the two groups of patients.